Kajian Penerapan Inovasi Pada Usahatani Nilam di Desa Matabondu Kecamatan Angata Kabupaten Konawe Selatan - Ima Fatmawati; Usman Rianse; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2022)
This study aims to determine : (1) find out how the farmers are applying the innovation in the cultivation of the patchouli plant in the village of Matabondu, Angata district, south Konawe regency, (2) find out the farmers’ application of the innovation in the cultivation of patchouli harversts in the village of matabondu, angata district, south konawe regency. The study was carried out in the village of Matabondu, Angata district, south Konawe regency which was held in November 2021 to complete 2022 with the number of 7 informants specified by purposive sampling. The data analysis used is qalitative descriptive. The results showed that the application of innovation performed farmers in the cultivation of the patchouli was at the stage of planting and treatment. Whereas the farmers’applicatiom of innovation in the patchouli harvest was at the stage of the harvest